1996
DOI: 10.1103/physrevlett.76.4250
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spin Dynamics in Ferromagnetic Nickel

Abstract: The relaxation processes of electrons and spins systems following the absorption of femtosecond optical pulses in ferromagnetic nickel have been studied using optical and magneto-optical pump-probe techniques. The magnetization of the film drops rapidly during the first picosecond, but different electron and spin dynamics are observed for delays in the range 0-5 ps. The experimental results are adequately described by a model including three interacting reservoirs (electron, spin, and lattice).[S0031-9007(96)0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

73
2,010
7
14

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,234 publications
(2,104 citation statements)
references
References 15 publications
73
2,010
7
14
Order By: Relevance
“…This first observation of an ultrafast magnetization enhancement in the Fe layer can be explained by superdiffusive spin transport 12,13 (see also Supplementary Discussion), taking place on timescales comparable to the demagnetization processes explored in earlier works [1][2][3]5 . The mechanism we propose for enhancement of the magnetization is based on filling of majority spin states above the Fermi energy in the Fe layer by majority spins coming from Ni.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This first observation of an ultrafast magnetization enhancement in the Fe layer can be explained by superdiffusive spin transport 12,13 (see also Supplementary Discussion), taking place on timescales comparable to the demagnetization processes explored in earlier works [1][2][3]5 . The mechanism we propose for enhancement of the magnetization is based on filling of majority spin states above the Fermi energy in the Fe layer by majority spins coming from Ni.…”
Section: Resultssupporting
confidence: 58%
“…Spin dynamics is in-itself of fundamental interest for understanding spin-photon-charge-phonon interactions and their complex interplay on femtosecond to picosecond timescales. The potential to rapidly manipulate spins was first demonstrated in a pioneering experiment 1 on Ni that observed that the magnetization of 3d ferromagnets can be optically quenched within 50-300 fs after excitation by a femtosecond laser pulse 2,3 . This ultrafast demagnetization is then followed by a slower magnetization recovery on picosecond timescales.…”
mentioning
confidence: 99%
“…2c, radial intensity profiles are plotted for different pump-probe time delays. The relation between real space distances, r x y = + 2 2 , and wave vector transfer, q, is given by equation (1). A comparison of these curves reveals that peak position and shape remain unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…It reproduces the general behaviour previously observed for transition metal-based ferromagnetic materials 2 , namely, a very fast initial demagnetization on the timescale of a few hundred femtoseconds followed by a slow partial recovery. This behaviour is described by the phenomenological three temperature model proposed for uniformly magnetized films 1 . The electronic system is heated by the optical excitation almost instantaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation